Earnings disparities and income inequality in CEE countries: an analysis of development and relationships - Vecernik, Jiri (Luxembourg, 2010)
"The potential in survey data for the study of simultaneous changes in earnings disparities, inequality of household income, and the connections between them has thus far been underexploited. This paper presents various data on four Central and East European (CEE) countries and, for the sake of comparison, partially on Austria and Germany. First, I compare the changes in both distributions over time since the communist period as reported in various sources and ask: how much did disparities and inequalities increase during the transition? Second, I present some methodological and empirical attempts that have been made so far to analyse the connections between the two distributions and ask: how should the association between personal and household earnings be analysed and what do we know about its development? Third, I present the changing links between earned and disposable income in CEE countries using LIS data for history and EU-SILC data for the present time. Here the question is: how strong was and currently is the association in CEE countries and how do they differ in packaging family income? Two perspectives are used: employed persons (examining the association between their earnings and the income of the households they live in) and employee households (examining the sources of their income by decomposing their inequality). Various sources confirm that earnings disparities and income inequalities rose more or less in all four CEE countries after 1989. This is apparent in the individual countries in various phases of their transition. In contrast, no increase occurred from 2004 to 2007, according to the EU-SILC surveys."